Thailand Adolescent Birth Rate: Trend and Related Indicators - Bunyarit Sukrat (The Royal Thai College of Obstetricians and Gynaecologists, 2014)
Objectives:To describe trend of adolescent birth rate and related indicators in Thai population.Material and Method: Three national and international secondary databases were used. The data was described by descriptive statistics in term of number, rate and proportion.Results: According to Thailand Public Health Statistics, Thailand adolescent birth rate decreased from 42.2 per 1,000 women aged 15-19 in 1990 to meet the lowest rate of 31.1 in the year 2000. After that, the adolescent birth rate has steadily increased. The latest data in 2012 shows that Thailand adolescent birth rate is 53.8 per 1,000 women aged 15-19. There are some discrepancies between adolescent birth rate reported by Thailand Public Health Statistics and the 2012 update for MDG database because of different calculation methods.Conclusions: Thailand adolescent birth rate is still in the increasing trend.